DENTOALVEOLAR PROFILE CHANGES AFTER MALOCCLUSIONS TREATMENT WITH AND WITHOUT EXTRACTION: PERUBAHAN PROFIL DENTOALVEOLAR SETELAH PERAWATAN MALOKLUS DENGAN DAN TANPA PENCABUTAN GIGI - I Gusti Aju Wahju Ardani (TALENTA, 2012)
Treatment protocol in orthodontic treatment is based on the dentoalveolar and facial profile patients. The objectives of thisstudy were (1) to compare dentoalveolar profile changes in skeletal malocclusion types after four orthodontic treatmenttypes, nonextraction, two upper first premolars, two lower first premolars extraction, and four first premolars extraction;(2) to compare dentoalveolar profile changes after orthodontic treatment within skeletal malocclusion types; (3) tocompare dentoalveolar profile changes within orthodontic treatment types. The study was conducted in Dental Hospital,Faculty of Dentistry-Airlangga University. Forty eight patients (females, between 17-32 years) who fulfilled the inclusioncriteria were selected. Data was analyzed using ANOVA test. The results showed that dentoalveolar profile wassignificant difference between without extraction and four first premolars extraction (p<0.05), except for variables NB-L1and IMPA. The dentoalveolar facial profile changes were significant difference within malocclusion types afterorthodontic treatment (p<0.05). In Conclusion, the extraction in orthodontic treatment type had a great variation ofdentoalveolar profile changes after orthodontic treatment depends on malocclusion types.